REDE GLOBO DE TELEVISÃO NO TERRITÓRIO BRASILEIRO: SISTEMA DE EMISSORAS AFILIADAS - Munhoz, Eliane Regina (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2013)
The system of broadcast affiliated of Rede Globo Television consolidated in the Brazil in the 1970s, in the scientific and technical information era, with the intensification of technical, informational and normative densities within the national territory. The company, in order to organize this system, established a territorial division of labor that transforms the affiliates in the production units of information to headquarters, while it produces the bulk of programming that is transmitted by affiliates. The existence of a technosfera and a psichosfera creates the conditions so that this system operates with a high territorial capillarity and vertically imposes its transmition everywhere.